2009
DOI: 10.1007/bf03245850
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of oxidation of aniline and substituted anilines by isoquinolinium bromochromate in aqueous acetic acid

Abstract: Oxidation of anilines by isoquinolinium bromochromate (IQBC) in aqueous acetic acid leads to the formation of corresponding azobenzenes. The reaction is first order with respect to both aniline and IQBC and is catalyzed by hydrogen ion. The rate of oxidation decreases with increasing dielectric constant of solvent, indicating the presence of an ion-dipole interaction. The rate of oxidation decreases with increase in concentration of KCl, possibly due to the formation of less reactive species by interaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The oxidation kinetics of anilines by various oxidizing agents have been extensively studied [10][11][12][13][14] . Since anilines are very harmful to human health and the environment, removal of aniline from the environment is the ultimate goal of research today.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation kinetics of anilines by various oxidizing agents have been extensively studied [10][11][12][13][14] . Since anilines are very harmful to human health and the environment, removal of aniline from the environment is the ultimate goal of research today.…”
Section: Introductionmentioning
confidence: 99%
“…Since the plot of log k 1 versus log [H + ] did not give an ideal slope of unity. It is not possible to take the order with respect to [H + ] as one and it can be concluded that the reaction is simply an acid catalyzed one 36 . (Table 4).…”
Section: Effect Of Varying the Ionic Strengthmentioning
confidence: 99%
“…The activation parameters Ea, ∆H # , ∆S # and ∆G # have been calculated from the slope of the straight line and found to be 0.401 kJmol −1 , 2.47 kJmol −1 , −28.38 Jmol −1 K −1 and 10.93 kJmol −1 respectively. The negative value of entropy indicates that the structure of the activated complex is more ordered those of the reactants [29]. The value of activation Gibbs energy is positive that indicates that the formation of the activated complex is not spontaneous which results in slowing down the reaction.…”
Section: Kinetic Studiesmentioning
confidence: 99%